2023
DOI: 10.7717/peerj.15381
|View full text |Cite
|
Sign up to set email alerts
|

Association between INHA gene polymorphisms and litter size in Hainan black goats

Abstract: Background The inhibin alpha (INHA) gene is one of the important genes affecting the reproductive traits of animals. Hainan black goats are the main goat breed in Hainan Island (China), whose development is limited by low reproductive performance. However, the relationship between INHA gene and the reproductive performance of Hainan black goats is still unclear. Therefore, the purpose of this work was to explore the effect of INHA gene polymorphisms on the litter size of Hainan black goats. Methods Single nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…According to Liu et al [ 51 ], APOA1 , AMH , TAC3 , INHA , SPARC , and SOX9 were identified as sexually immature marker genes for Mongolian horses due to their specific expression patterns associated with sexual immaturity. These proteins play crucial biological roles in various processes such as cell differentiation, tissue development, and hormonal regulation, which are integral to the sexual immaturity stage [ 52 , 53 , 54 , 55 , 56 ]. On the other hand, PRM1 , PRM2 , H1-9 , PRSS37 , and HMGB4 were selected as sexually mature marker genes based on their expression profiles linked to sexual maturity.…”
Section: Discussionmentioning
confidence: 99%
“…According to Liu et al [ 51 ], APOA1 , AMH , TAC3 , INHA , SPARC , and SOX9 were identified as sexually immature marker genes for Mongolian horses due to their specific expression patterns associated with sexual immaturity. These proteins play crucial biological roles in various processes such as cell differentiation, tissue development, and hormonal regulation, which are integral to the sexual immaturity stage [ 52 , 53 , 54 , 55 , 56 ]. On the other hand, PRM1 , PRM2 , H1-9 , PRSS37 , and HMGB4 were selected as sexually mature marker genes based on their expression profiles linked to sexual maturity.…”
Section: Discussionmentioning
confidence: 99%